Mysteries of mankind [videorecording] - Jampel, Barbara; Kane, Dennis B.; Skinner, Thomas; National Geographic Society; WQED (Television station : Pittsburg, Pa.). ([Washington, D.C.] The Society Columbia Tristar Home Video [distributor]., 1988)
Traces the development of human evolution and establishes relationships among ancestral species. Explains evolution in association with tool making from human paleontological studies in Africa, England, and Israel.
VHS.
Narrated by Richard Kiley; Photographed by Erik Daarstad ... [et al.]; edited by John Dabney.
Keywords: Human evolution; Man, Prehistoric -- Tools; Anthropology